Liver metastases from colorectal cancer: radioembolization with systemic therapy. - Nicolay, N; Berry, D; Sharma, R (2009)
The majority of patients with advanced colorectal cancer die from hepatic metastases caused by disease progression; therefore, several novel technologies are in clinical development to potentially improve local control of liver disease. Radioembolization is a technique for administering radiotherapy internally to unresectable primary or secondary hepatic malignancies in a single procedure. This technique involves the injection of resin or glass microspheres that contain (90)Y into the arterial supply of the liver. Clinical trials of radioembolization used with concomitant radiosensitizing chemotherapy have shown promising results in patients with metastatic colorectal cancer. Several reports suggest that radioembolization is associated with significant downsizing of liver metastases to permit subsequent surgical resection. In this article, the rationale for combining radioembolization with the cytotoxic and molecularly targeted agents licensed for the systemic treatment of colorectal cancer is outlined. Clinical data from trials of radioembolization with concomitant systemic treatment are reviewed, with an emphasis on the appropriateness of primary end points in large-scale trials and the practical aspects of surgical resection in patients whose tumors are successfully downsized by this chemoradiation approach.